2010
DOI: 10.2136/sssaj2009.0092
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide and Carbon Dioxide Emissions Following Green Manure and Compost Fertilization in Corn

Abstract: Remogna for their technical assistance. We also extend our appreciation to the anonymous reviewers who provided useful suggestions for improvement of this paper. This publication is the result of a FISR project funded by the Italian Ministry of Agriculture and Forestry. 1Mitigating the impact of fertilization on global warming: can leguminous green manure and compost help to reduce N 2 O and CO 2 emissions? ABSTRACT Alternative nitrogen fertilizers that stimulate low greenhouse gas emissions from soil are need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 114 publications
7
70
0
2
Order By: Relevance
“…Variations in WFPS between incubated soils should impact emissions of CO 2 , but all soils were collected at a time of the year where climate was conducive to wet soil conditions and low evapotranspiration. With the preconditioning, all soils were incubated at a constant moisture level near field capacity, and under those conditions, the CO 2 emissions are little affected by soil moisture (Chantigny et al 1999;Ruser et al 2006;Alluvione et al 2010).…”
Section: Incubation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in WFPS between incubated soils should impact emissions of CO 2 , but all soils were collected at a time of the year where climate was conducive to wet soil conditions and low evapotranspiration. With the preconditioning, all soils were incubated at a constant moisture level near field capacity, and under those conditions, the CO 2 emissions are little affected by soil moisture (Chantigny et al 1999;Ruser et al 2006;Alluvione et al 2010).…”
Section: Incubation Studymentioning
confidence: 99%
“…Methods such as reducing N fertilizer to optimum rates for corn (Zea mays L.) production have been recommended for mitigating GHG emissions due to its large direct effect on N 2 O fluxes (Snyder et al 2009;Millar et al 2010;Shcherbak et al 2014;Stuart et al 2014). Although this strategy may be effective, it is unclear how alternative N fertilization will impact CO 2 emissions, as studies have shown contrasting results (Rochette and Gregorich 1998;Mosier et al 2006;Wilson and Al-Kaisi 2008;Alluvione et al 2009Alluvione et al , 2010Venterea et al 2010;Sainju et al 2012). A meta-analysis on 257 studies looking at the effect of soil N addition on soil respiration suggests a substantial stimulation of soil respiration (16%) and an enhancement in soil C mineralization (6%) within agricultural ecosystems (Lu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the design of control treatments in the literature did not have uniform rule. For instance, Dusenbury et al (2008) established uncultivated grass system as their control plot (no fertilizer, crop and irrigation) for deriving EFs of fertilizer crop fields in a wheat field, while others only mentioned unfertilized or without fertilization and crop residual as the control plots in agricultural fields (Zou et al, 2005b;Alluvione et al, 2010;Ma et al, 2010). Our incipient understanding about the control treatment was that the influence of human activities on the field was as small as possible, and thus, the field without crop and irrigation was designed as the control plot which was similar with the design of Dusenbury et al (2008).…”
Section: Experimental Designmentioning
confidence: 99%
“…The extent of management effects on soil greenhouse gas emissions is a large source of uncertainty in grasslands (Soussana et al 2004). Manure amendment can increase CO 2 and N 2 O fluxes (Chadwick et al 2000, Dalal et al 2003, Mosier et al 2004, Davidson 2009); composted animal waste and plant matter tends to result in lower greenhouse gas emissions relative to green manures or synthetic fertilizers (Vallejo et al 2006, Alluvione et al 2010. However, the effects of organic matter additions on greenhouse gas dynamics in rangelands are largely unstudied (Lynch et al 2005, Cabrera et al 2009).…”
Section: Introductionmentioning
confidence: 99%